2018 55th ACM/ESDA/IEEE Design Automation Conference (DAC) 2018
DOI: 10.1109/dac.2018.8465918
|View full text |Cite
|
Sign up to set email alerts
|

ThUnderVolt: Enabling Aggressive Voltage Underscaling and Timing Error Resilience for Energy Efficient Deep Learning Accelerators

Abstract: Hardware accelerators are being increasingly deployed to boost the performance and energy efficiency of deep neural network (DNN) inference. In this paper we propose Thundervolt, a new framework that enables aggressive voltage underscaling of high-performance DNN accelerators without compromising classification accuracy even in the presence of high timing error rates. Using post-synthesis timing simulations of a DNN accelerator modeled on the Google TPU, we show that Thundervolt enables between 34%-57% energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 34 publications
1
98
0
Order By: Relevance
“…It has been shown that NNs are inherently resilient [27], [28], [29]; however, the ever-increasing fault rate in nanoscale technology nodes necessitates further studies in this area to explorer better trade-off of reliability, power, energy, and performance. Hence, in recent years NN resilience is studied with different approaches, e.g., software-level simulations or theoretical analyzes [30], [31], SPICE simulations [4], [32], [33], and experimenting on the real hardware operating on low-voltage regimes [34], [35], [36]. Among them, it is evident that software-level simulations and theoretical analyzes lack the information of the underlying hardware platform and are relatively less precise.…”
Section: A Different Methodologies To Study Nn Resiliencementioning
confidence: 99%
“…It has been shown that NNs are inherently resilient [27], [28], [29]; however, the ever-increasing fault rate in nanoscale technology nodes necessitates further studies in this area to explorer better trade-off of reliability, power, energy, and performance. Hence, in recent years NN resilience is studied with different approaches, e.g., software-level simulations or theoretical analyzes [30], [31], SPICE simulations [4], [32], [33], and experimenting on the real hardware operating on low-voltage regimes [34], [35], [36]. Among them, it is evident that software-level simulations and theoretical analyzes lack the information of the underlying hardware platform and are relatively less precise.…”
Section: A Different Methodologies To Study Nn Resiliencementioning
confidence: 99%
“…Hence, recently, the resilience of DNNs has been studied in different abstraction levels. A vast majority of the previous works in this area belong to the DNN inference phase, including simulationbased efforts [33]- [36] and works on the real hardware [12], [37]- [39]. The verification of the simulation-based works on the real fabric can be a crucial concern; also, the real hardware works are mostly performed on the customized ASICs, which of course, reproducing those results on the COTS systems is a crucial question.…”
Section: Related Workmentioning
confidence: 99%
“…Third, works that study approximate arithmetic logic in DNN workloads [141,141,178,179]. ThUnderVolt [178] proposes to underscale the voltage of arithmetic elements. Salami et al [141] and Zhang et al [179] present fault-mitigation techniques for neural networks that minimize errors in faulty registers and logic blocks with pruning and retraining.…”
Section: Related Workmentioning
confidence: 99%